TUTURAN BERMAKNA IMPERATIF DALAM NOVEL RINDU KARYA TERE LIYE - Fally Mawar Wilujeng; Mangatur Sinaga; Charlina ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study, entitled Meaningful Imperative Speech In a Novel Rindu By Tere Liye. This study aimed to describe the meaningful imperative speech in a novel rindu by tere liye. The research is a qualitative research with descriptive methods. Data of this study is a meaningful imperative speechboth in imperative speech, declarative speech, and interrogative speech. Data obtained using the technique read, technique note and validity of the data was acquired through triangulation technique. Than, data was analyzed by indentifying, classifying the data based on the meaning imperative speech.Based on the data analysis has been done, the authors found a significant meaningful imperatives speech of imperative speech much eight that is imperative command, messenger, requests, insistence, persuasion, crosslegged, impulsive, and prohibition. Than, declarative speech stating the meaningful imperative speech much five that is imperative messenger, impulsive, requests, cross-legged,and prohibition.And interogative speech stating the meaningful imperative speech much five that is imperative command, impulsive, requests, cross-legged,and prohibition.Key Words: imperative speech meaningful imperative, declarative speech meaningful imperative, and interogative speech meaningful imperative.